Evaluation of school health services in selected public senior secondary schools in Egbeda Local Government Area of Oyo State. (2012)
School health services is one of the components of school health programme and is a powerful means of raising community health, especially in future generations. This study examined the availability of school health services in selected public senior secondary schools in Egbeda Local Government Area of Oyo State. Descriptive survey research method was adopted, 300 participants were selected in six selected schools through simple random sampling method. The instrument used was a self- developed validated questionnaire with a reliability coefficient r = 0.74, five hypotheses were generated, chi-square statistics was used to analyzed the collected data at 0.05 alpha levels. All the hypotheses were accepted. Based on the findings, the following recommendations were made: that the government at various levels and the school authorities should make provision for effective school health services such as appraisal and medical examination, provision of adequate midday meal, care of emergencies, referral and follow up services, as well as immunization to prevent the spread of communicable diseases and promotion of sound health among students and staff in public secondary schools.